THE EFFECTIVENESS OF USING SPEAKING ACTIVITIES FOR INTERMEDIATE LEVEL LEARNERS: THE EFFECTIVENESS OF USING SPEAKING ACTIVITIES FOR INTERMEDIATE LEVEL LEARNERS - Kalbaeva, Umida (Журнал иностранных языков и лингвистики, 2025)
Speaking plays a fundamental role in language acquisition, serving as both cognitive and communicative process that facilitates linguistic development. It enables learners to actively engage with the target language, practice linguistic structures, and enhance overall proficiency. In teaching English the students should be taught not only to have knowledge on particular subjects as grammar, speaking, writing, listening etc. but they also should have been introduced with educational-upbringing materials on, for instance, culture, moral, customs and rituals of every-day-use of the people living in English speaking countries [1; 56]. Various theoretical perspectives highlight the significance of speaking in language learning, emphasizing its role in interaction, cognitive processing, fluency development, and motivation.